HERO (Helping and Empowering Women): Dukungan Pra-Konsepsi untuk Perempuan Usia Reproduksi - Novembriani, Rizqie Putri; Andyastanti, Tisnalia Merdya; Hasanah, Winny Kirana; Puriastuti, Alifia Candra; Aghnani, Almira Dwi; Desyasti, Falaah Azurra; Rahmawati, Zulfa; Suprobo, Nina Rini (Jurnal SOLMA, 2025)
Background: The HERO (Helping and Empowering Women in Reproductive Choices) program is a community service initiative aimed at enhancing the knowledge of women of reproductive age in Sumbersekar Village, Dau District, Malang Regency. A situational analysis of Midwife Sunarni’s practice revealed significant challenges: a shortage of adequately trained village health cadres to support healthcare professionals in delivering reproductive health education and low community awareness stemming from educational and economic factors. Method: Conducted in September 2024 and through two educational sessions involving village health workers and women of reproductive age, the program provided information on family planning, reproductive health, and preconception nutrition. Participants completed pretests and posttests to assess knowledge improvement before and after the sessions. Result: Results showed a significant increase in the average posttest score (89.80) compared to the pretest score (57.80). The distribution of knowledge levels also indicated a rise in the "high" category from 0% in the pretest to 76% in the posttest. This program successfully demonstrated the effectiveness of education in improving preconception health knowledge among women of reproductive age. Follow-up and monitoring by village health workers are necessary to sustain the knowledge and healthy behaviors promoted by the program. Conclusion: It is important to build on the success of the HERO initiative by implementing ongoing education programs and addressing remaining knowledge gaps.